PENGARUH KONSENTRASI BEESWAX SEBAGAI EMULGATOR PADA KARAKTERISTIK DAN STABILITAS FISIK SEDIAAN KRIM PATI BENGKUANG (Pachyrhizus erosus L.) - Puspitasari, Dewi Fitriani; Ratih, Sekar Wida (Jurnal Buana Farma, 2025)
Starch of bengkuang tuber (Pachyrhizus erosus L.) has antioxidant activity, is able to provide moisture, antiaging , relieve inflammation so that it is efficacious to prevent skin cell damage due to free radicals. The formulation of bengkuang starch in cream form is expected to make it easier to use. The main component that affects the physical characteristics of a cream preparation is the emulgator. Beeswax is an emulgator that can improve cream consistency and stabilise the preparation. This study aims to determine the effect of different concentrations of beeswax on the physical characteristics and stability of bengkuang starch cream preparation. The research method begins with the collection of starch which is done by filtering the juice of the bengkuang tuber. The results of the filter were precipitated 24 hours and then the precipitate was dried. The cream was made in 3 formulas namely FI, FII and FIII with variations of beeswax 5, 10 and 15%, then tested for characteristics and physical stability. The results showed that increasing the concentration of beeswax caused the viscosity value of the cream preparation to increase, the spreadability value decreased and the adhesion value increased. The concentration of beeswax also affects the pH value of the preparation, namely the higher the concentration of beeswax, the pH value increases. The results of the physical stability test using the cycling test method for 6 cycles show that the cream preparations that are still stable are formula II and III.